Blood urea nitrogen and creatinine as prognostic indices in canine pyometra - PANDE, NISHI; PRABHAKAR, S; GANDOTRA, V K; SANGHA, S P S; NANDA, A S (The Indian Journal of Animal Reproduction, 2023)
Blood urea nitrogen (BUN) and creatinine were estimated in 20 bitches suffering from pyometra. Azotemia (BUN> 30mg/di and/or plasma creatinine > 2 mg/di) was recorded in l O (50%) patients. The bitches were treated with medicines and/ orsurgically for pyometra and their responses were studied. Death/complications occurred in 40 % of the azotemic bitches. Thebitches suffering from pyometra with initial plasma BUN and creatinine levels of more than 120 mg/di and 5 mg/di, respectively,had a poor prognosis.
Keywords: Blood urea nitrogen; creatinine; pyometra